2021
DOI: 10.1002/mrm.28799
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term behavioral effects observed in mice chronically exposed to static ultra‐high magnetic fields

Abstract: Purpose The primary goal of this study was to investigate whether chronic exposures to ultra‐high B0 fields can induce long‐term cognitive, behavioral, or biological changes in C57BL/6 mice. Methods C57BL/6 mice were chronically exposed to 10.5‐T or 16.4‐T magnetic fields (3‐h exposures, two exposure sessions per week, 4 or 8 weeks of exposure). In vivo single‐voxel 1H magnetic resonance spectroscopy was used to investigate possible neurochemical changes in the hippocampus. In addition, a battery of behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Consistent with previous research, our results also showed that 150 mT moderate intensity SMFs have a similar effect to ultra-high or high SMF [ 10 , 13 , 16 , 19 , 22 , 23 ]. For example, Lv et al found that time and distance in the center area, the number of entries to the center area and averaged velocity were reduced when compared immediately after 11.1–33.0 T 1 h exposure with sham in healthy male mice, whereas after a 2-week recovery, all these parameters changed from lower to higher [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous research, our results also showed that 150 mT moderate intensity SMFs have a similar effect to ultra-high or high SMF [ 10 , 13 , 16 , 19 , 22 , 23 ]. For example, Lv et al found that time and distance in the center area, the number of entries to the center area and averaged velocity were reduced when compared immediately after 11.1–33.0 T 1 h exposure with sham in healthy male mice, whereas after a 2-week recovery, all these parameters changed from lower to higher [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…For example, Kokoreva et al found that after the exposure (3 h/d) of 1.6 T SMF for 1 day, 5 days and 15 days, the swimming time of mice (unknown gender) was prolonged and exercise tolerance was enhanced [ 11 ]. Ivan Tkac et al found that 16.4 T SMF 4- or 8-week exposure (3 h/time, 2 times/week) did not affect cognition and motor function in female and male mice [ 19 ]. We found the SMF exposure time was short in the above research, and it is urgent to explore the biosafety and effect of long-term SMF exposure (continuous treat for several months) on females.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in the experimental protocols may explain the different results obtained in the two studies. In Tkáč et al, 14 the mice were moving freely in the 7 × 14 cm 2 holders in which they were exposed by groups of N = 2 animals, whereas in the current study, the mice were static during the exposure, as during human scanning. In Tkáč et al, 14 the mice were awake, whereas in the current study they were anesthetized.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, implanted deep brain stimulating electrodes appear to produce too localized a perturbation to alter the mind’s EMF, although effects on cognition do occur in some patients ( Agashe et al, 2022 ; Chang et al, 2022 ). It has long been known that high strength magnetic fields of MRI scanners effect both human and animal subjects, producing dizziness, altered behavioral responses and cognitive impairment ( Antunes et al, 2012 ; Tkáč et al, 2021 ). Weaker EMFs produced by cell phones, radios and headphones do not appreciably alter mental activity, although long-term exposure to these weak fields may disrupt some brain functions ( Bodewein et al, 2022 ; Schüz et al, 2022 ).…”
Section: Hypothesismentioning
confidence: 99%